Morphometry of the hippocampal microvasculature in post‐stroke and age‐related dementias. Issue 3 (April 2014) - Burke, M. J. C.; Nelson, L.; Slade, J. Y.; Oakley, A. E.; Khundakar, A. A.; Kalaria, R. N.
<x xml:space="preserve">Abstract</x> Background Optimal vascular function is vital for prevention of dementia. We hypothesized that elderly post‐stroke survivors who preserve cognitive function show unperturbed cerebral microvasculature compared with those who develop dementia. Methods Using stereological spherical probe software, we compared the length density (Lv, cumulative vessel length per unit tissue volume) of hippocampal microvessels in post mortem brain tissue from post‐stroke survivors, Alzheimer's disease (AD), vascular dementia (VaD) and normal ageing control subjects. We also assessed microvessel diameters in the same subjects. Microvessels were identified by markers of endothelial cells (glucose transporter 1; GLUT1), basement membrane (collagen IV; COL4) and smooth muscle cell α‐actin (SMA). Results We found increased Lv of both GLUT1 and COL4 immunostained microvessels (P < 0.05) in the hippocampal CA1 region of post‐stroke demented (PSD) and AD cases compared with post‐stroke nondemented (PSND), control and VaD subjects. However, no changes were apparent in the CA2 region. We also noted significant increase in Lv in the entorhinal cortex of AD compared with PSND and PSD subjects. The mean diameter of microvessels was decreased in PSD, compared with PSND, as well as in AD and VaD compared with controls. Cumulative frequency analysis showed PSND subjects to have significantly greater proportion of microvessels with diameters, ranging from 7 to 12 μm. Conclusions An increase in microvascular Lv in AD and PSD suggests either an increase in angiogenesis or the formation of newer microvessel loops in response to cerebral hypoperfusion. The decreased vessel diameters found in AD and VaD suggests increased vasoconstriction in dementia.